Optical solitons to the fractional Schrödinger-Hirota equation - Sulaiman, Tukur Abdulkadir; Bulut, Hasan; Atas, Sibel Sehriban (Applied mathematics and nonlinear sciences, 2019)
This study reaches the dark, bright, mixed dark-bright, and singular optical solitons to the fractional Schr dinger-Hirota equation with a truncated -fractional derivative via the extended sinh-Gordon equation expansion method. Dark soliton describes the solitary waves with lower intensity than the background, bright soliton describes the solitary waves whose peak intensity is larger than the background, and the singular soliton solutions is a solitary wave with discontinuous derivatives; examples of such solitary waves include compactions, which have finite (compact) support, and peakons, whose peaks have a discontinuous first derivative. The constraint conditions for the existence of valid solutions are given. We use some suitable values of the parameters in plotting 3-dimensional surfaces to some of the reported solutions.